2024
DOI: 10.5802/crgeos.187
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the coupled heterogeneities of the lacustrine microbialite-bearing carbonate reservoir of the Yacoraite Formation (Salta, Argentina)

Abstract: The Yacoraite Formation is a complex lacustrine microbialite-bearing carbonate formation whose heterogeneity is due to different sedimentary facies associations and several microbialite geobodies. The bi-variate plurigaussian geostatistical method is applied to simulate in parallel these two types of heterogeneity in a 3D reservoir-scale geological model. Each variable is simulated by a complete plurigaussian method based on geological interpretation and field observations and quantifications. They are coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The stratigraphic architecture of the Yacoraite Fm. was primarily controlled by climate changes [30,38] and the sedimentation pattern and stratigraphic framework are characterised by multiple hierarchies of cyclicity [30,38,[57][58][59]63,[76][77][78][79]. The present study considers the mid-term cyclicity reported by [30,38] for the Metán-Alemania sub-basins.…”
Section: Geological Contextmentioning
confidence: 99%
“…The stratigraphic architecture of the Yacoraite Fm. was primarily controlled by climate changes [30,38] and the sedimentation pattern and stratigraphic framework are characterised by multiple hierarchies of cyclicity [30,38,[57][58][59]63,[76][77][78][79]. The present study considers the mid-term cyclicity reported by [30,38] for the Metán-Alemania sub-basins.…”
Section: Geological Contextmentioning
confidence: 99%
“…Chihi et al [2023] present a geostatistical analysis of a multiscale groundwater reservoir system, combining geological-geophysical investigations, geostatistics, and 3D geological modelling in the Jeffara basin of southeast Tunisia. The behaviour of a complex heterogeneous lacustrine carbonate formation in Argentina is modelled by Teles et al [2023], using a bivariate plurigaussian geostatistical method to constrain the porosity simulation. Last, de Fouquet and Nos [2023] discuss the cokriging of transmissivity using head measurements and show that the estimation is improved in comparison with the case of head data from a single flow.…”
mentioning
confidence: 99%